Case reportsComplex percutaneous coronary intervention of the left coronary artery with rotational atherectomy in an 84-year-old dialysed patient - Zalewska-Adamiec, Małgorzata; Kralisz, Paweł; Bachórzewska-Gajewska, Hanna; Dobrzycki, Sławomir (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Coronary artery disease in patients with end-stage renal disease occurs several dozen times more often than in the general population. Atherosclerotic changes in coronary arteries in dialysed patients are more diffused and calcified, which hampers the percutaneous coronary angioplasty. We present a case of an 84-year-old dialysed patient, in whom complex percutaneous coronary intervention of the left anterior descending artery was performed with the use of rotational atherectomy.